Preparasi dan Karakterisasi Katalis Mo-Ni/HZ dengan Metode Impregnasi untuk Cracking Katalitik Minyak Limbah Cair Pengolahan Kelapa Sawit menjadi Bahan Bakar Nabati - Shinta Lestari; Agus Sundaryono; Rina Elvia (ALOTROP, 2019)
This study aims to determine the characteristics of Mo-Ni/HZ catalysts and test the ability of Mo-Ni/HZ catalysts in converting vegetable oils into biofuels through catalytic cracking reactions.Catalyst preparation is carried out by the impregnation method which begins with activation of natural zeolite.Impregnation is carried out by dissolution, reflux, filtration, drying and calcination.Catalyst characterization included the determination of the distribution of metals in zeolites using IR spectroscopic analysis and total acidity of the catalyst by ammonia adsorption gravimetric method.Preparation of samples prior to cracking is heating, degumming and bleaching.Catalytic cracking was carried out at 280oC using Mo-Ni/HZ catalyst for 100 minutes.The constituent components of the cracking results were analyzed by GC-MS and IR spectroscopy.The results obtained from the catalytic cracking process were then determined by physical characteristics which included density, viscosity, fog point and pour point test.Based on the shift of wave number in IR spectroscopy, it can be concluded that the Ni and Mo metals are embedded in the HZ.This Mo-Ni/HZ catalyst has total acidity of 8.39 mmol/gammonia.The results of the study prove that the Mo-Ni/HZ experiment proved to be able to crack oil frompalm oil processing wastewater by 91.46% to composition C=O ester CH aliphatic.The physical characteristics of cracking productshave parameters density of 0.93 g/cm3, a viscosity of 26.60 cSt, a fog point of 15oC and pour point of 11.67oC.